Biliary atresia in Slovenia Congenital extrahepatic biliary atresia in children in Slovenia – epidemiological retrospective data - Petja Fister (Zdravniški Vestnik, 2013)
Backg round: The objective of this study was to investigate the history, clinical, laboratory, imaging data and outcome of children with biliary atresia in Slovenia. Methods: In an epidemiological single-arm retrospective study health records of infants born in Slovenia between October 1996 and October 2011, who were diagnosed with biliary atresia at the University Children’s Hospital, University Medical Centre Ljubljana, were reviewed. Epi-demiological data and outcomes of patients with biliary atresia in Slovenia were studied. Results: In the 15-year period, 16 cases of biliary atresia were confirmed (1/20000 newborns). Two thirds of patients in our cohort were females. One child had associated laterality malformation. The majority of patients were born in autumn and winter months. The affected newborns were born mature with appropriate birth measures and healthy, but most of them became jaundiced in the first days of life. Primary surgery was done in 11 children at median age of 70 days. Of those children in whom the surgery was unsuccessful, 13 (81 %) underwent liver transplantation in foreign surgical centres. Median age at liver transplantation was 9 months, median time from Kasai operation to liver transplantation was 5 months. Median follow-up was 9.75 years (range 1.2–15.4). Conclusions: In Slovenia, the incidence of biliary atresia is low and biliary atresia splenic malformation very rare. The observed seasonal incidence might suggest the viral aetiology.